DEVELOPING STUDENT COMPETENCIES THROUGH AN INTERNSHIP PROGRAM IN THE STRATEGIC PLANNING DIVISION AT PT.PELINDO MULTI TERMINAL - Muhammad Elvin Lubis; Siti Radinda Azzahra Siregar; Tegar Abdul Fatah; Muhammad Multazam (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2024)
The internship program conducted from March 25 to June 24, 2024, at PT Pelabuhan Indonesia (Pelindo Multi Terminal ), located at Jalan Lingkar Pelabuhan No.1, Belawan II, Medan Belawan City, Medan City, North Sumatra 20411, specifically in the Strategic Planning Department, is a crucial initiative in developing the competencies of management students from the University of North Sumatra (USU). The methods used in this specialized internship program are summarized in three stages: 1) preparation stage, 2) implementation stage, and 3) evaluation stage, including the final report. The internship aims to provide practical experience in strategic planning, business analysis, and project management. Through this internship, students are involved in the company's long-term planning activities, including business environment analysis, strategy development, and strategic evaluation. Emphasis on the development of soft skills such as communication, teamwork, and problem-solving is also a main focus. The results of this internship show a significant improvement in data analysis capabilities, participation in strategic meetings, document management, and the preparation of comprehensive final reports.